Varieties of Avicennian arguments for the existence of God. (October 2022) - Morvarid, Mahmoud
Abstract: In his The Salvation and The Remarks and Admonitions, Avicenna presents a well-known argument for the existence of God as a necessary being by itself. I will suggest, first of all, that the two pivotal notions employed in the argument, namely those of a necessary being by itself and a contingent being by itself, can be construed in different ways, leading to different versions of Avicenna's argument. I then turn to a specific version of the argument which seeks to show that there is at least one independently existing entity. This version constitutes the core of other versions of Avicenna's argument. Next, I shall explore how one might move from the existence of an independently existing entity to that of a necessary being by itself (variously construed). Finally, I will argue that the Avicennian argument for an independently existing entity suffers from a severe problem in that it fails to take account of the possibility of many-to-one causal relation.